Cloning and protein expression of human Annexin V homo-dimer recombinant protein (Journal of Hama University, 2022)
Annexin-V (ANXV) is widely used as an excellent probe to mark apoptosis, which can bind with high affinity to phosphatidylserine (PS) in the presence of calcium ions. This study aimed to design a new system for protein expression of ANXV as fusion with hCH3 dimerization domain in order to produce ANXN homo-dimer. This included the construction of the pRSET-hCH3-ANXV plasmid by cloning hCH3 gene with 6×His tag upstream the N-terminal of ANXV gene in the T7 promoter-plasmid pRSET. The expressed CH3-ANXV protein from this plasmid in the cytoplasm of E. coli was purified using metal affinity chromatography, as shown after SDS-PAGE separation and blue gel staining and detected by ELISA and immunoblotting using ANXV-specific polyclonal antibodies. ANXV homo-dimer protein will provide an efficient tool for PS binding with high affinity, and can be used after fluorescein labelling as rapid, sensitive and molecular tool for PS detection on membranes of either apoptotic cells or exosomes